EVALUASI SISTEM KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU (PPDB) BERBASIS ZONASI - Makmur Makmur (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This study discusses the evaluation of the new student admissions policy system based on zoning at the high school level in Palopo. The purpose of this study was to find out how the new student admissions policy system at the high school level in Palopo, and to find out how the implementation and social problems caused by the implementation of new student admissions based on zoning at the high school level in Palopo. The type of research used is qualitative research. Data were collected using primary data and secondary data in the form of literature studies, books, journals, magazines, newspapers, and previous research relevant to the research topic. The results of the study on new student admissions (PPDB) zoning are very good to be maintained by the government because they provide a positive value to the world of education. some positive values of PPDB zoning implementation are 1). Eliminating the term excellent and non-preferred schools. 2). There was an even distribution of students in every school 3). The Students very easy to get school because their homes are close to schools 4). Students whose IQ is not too good can study in schools with good quality education 5). Provide equal opportunities for parents to send their children to schools that have superior quality graduates. and 6). Economic Efficient.